When dams are built on shaky grounds.: Policy choice and social performance of hydro-project based development in Turkey - Öktem, Kerem (ERDKUNDE, 2002)
This paper investigates the driving forces behind and the continuities of state policy and social performance of hydro-project based development and, as its consequence, development-induced displacement in Turkey since the late 1950s. The investigation rests upon archival work in state institutions, expert interviews with decision-makers in implementing state agencies and in-depth interviews with people affected by large dam projects. Comparing the case of Turkey’s first large dam, Keban, with the recent Southeast Anatolia Project (GAP), it also draws on the recent work of the World Commission of Dams on the social impact of large hydro-projects and aims at contributing to the debate of development-induced displacement. The paper argues that in Turkey, despite methodological changes in the implementation of large dam projects and the introduction of notions of sustainable development, state policies related to regional development have stayed largely unimproved for the last forty years. The Southeast Anatolia Project, was initiated at the height of a Kurdish separatist insurgence in 1989, as an integrated regional development scheme in addition to the projects of 22 dams, several power stations and irrigation schemes, which had been planned in the 1970s and 1980s. Its aim was to alleviate regional income disparities through increased agricultural cash-crop production on irrigated soils. So far, however, it appears to have failed in kicking of a process of equitable wealth generation and in preventing processes of displacement, migration and dis-empowerment of local peasant communities, suggesting great similarities with the impact of the Keban Dam, which was completed in 1974. The assertion shared by many authors, various central government agencies and political actors in Turkey, that the GAP project might provide an effective panacea to Kurdish separatism therefore appears to be highly questionable. To the contrary, it might be claimed that rather than alleviating the extreme development disparities between the relatively industrialised Western parts of the country and the poor, disenfranchised and until recently war-ridden Southeastern region, the GAP project has, at most, delayed but not reversed the processes of displacement and massive migration towards regional urban centres. Due to the continuous experiences of displacement, migration and proletarianisation of predominantly Kurdish rural populations at the fringe of urban centres in the Southeast, this development orthodoxy has come under increasing criticism and pressure from European governments, on whose export credit guarantees the completion of the GAP project ultimately depends. Therefore, it is concluded, the current funding crisis of the project may now provide an opportunity to reflect and reconsider some of the basic shortcomings in Turkey’s hydropower-based development model for the Southeast and to respond to the grievances of the people, whose living conditions are to be improved by the GAP project in the first case.